PERKAWINAN BEDA AGAMA - Benedictus Hasan (Aggiornamento, 2021)
This paper focuses on the elaboration of interfaith marriages in canon law and civil law. The catholics as baptized people are members of the Universal Church. Because of this membership, they have to obey the Church rules. Simultaneously as a member of the Church who lives in a country, they also be bound by the civil law where they live. With the plural life context in the NKRI, it is not impossible for interfaith marriages to occur. Therefore, this paper intends to elaborate on the respective legal, canonical and civil policies. The method used in this paper is a comparative study by examining the policies of the applicable laws, with the aim of finding common ground, the extent to which the two laws accommodate the needs of their citizens. The findings of this paper are canonical law explicitly legalizes religious marriage with certain considerations and conditions. While civil law does not explicitly state it. Civil law only 'gives a gap' for the implementation of interfaith marriages.